Pulse Pressure Relationships with Demographics and Kidney Function in Ashanti, Ghana. (4th October 2018) - Banerjee, Debasish; Plange-Rhule, Jacob; Chitalia, Nihil; Kumi, Kwabena; Micah, Frank B.; Cappuccio, Francesco P.; Eastwood, John B.
Abstract : Introduction . Hypertension, particularly pulse pressure [PP] is a major risk factor for end-stage renal disease. However, the effect of individual components of hypertension namely PP, systolic [SBP] and diastolic blood pressure [DBP] on kidney function, in the general African population is unknown. Methods . Data were collected on 944 participants [aged 40-75 y], living in villages in the area around the city of Kumasi, Ghana, on demographics, medications, height, weight, BP and 24-hour creatinine clearance (CrCl). Results . The demographic and clinical characteristics were: age 55(11) [mean (SD)] years, females 62%, rural village-dwellers 52%, diabetes 1·5%, BMI 21(4) kg/m 2, 24-hourCrCl as a measure of glomerular filtration rate (GFR) 84(23) ml/min/1.73 m 2 . 29% had BP >140/90 mmHg; SBP and DBP were 125/74(26/14) mmHg, PP was 51(17) mmHg. PP increased with age by 0.55(95% CI: 0.46, 0.64) mmHg/year. PP was higher (53(17) v 49(15) mmHg; p < 0.001) in the semiurban participants. GFR decreased both with increasing PP [-0.19 (-0.27, -0.10 ml/min/1.73 m 2 /mmHg; p < 0.001] and SBP [-0.09 (-0.14, -0.03) ml/min/1.73 m 2 /mmHg; p < 0.001] but there was no significant relationship with DBP [-0.04 (-0.15, 0.06)]. After adjusting for SBP, the relationship between GFR and PP became steeper [-0.31 (-0.50, -0.12) ml/min/1.73 m 2 /mmHg; p < 0.001]. Using multivariate regression analysis that included PP, age, gender, BMI, only increasing age [-0.75 (-0.88, -0.62)] and decreasing BMI [0.49 (0.16, 0.81)] were associated with decreased kidney function. Conclusions . In this homogeneous West-African population, PP increased with age and had a steeper relationship with declining kidney function than SBP or DBP.